The Effect of Banking Liquidity Risk in the Financial Performance of Private Commercial Banks in Syria (Journal of Hama University, 2021)
The study aimed to identify the role of Liquidity risk in the financial performance of private commercial banks in Syria. To achieve this purpose, the annual data have collected from eleven private commercial banks during the period between 2008 -2018. The data were collected mainly from the financial reports of the banks.The independent variable represented by Liquidity risk was measured using the ratio of stable deposits to total deposits and the ratio of net loans to total deposits, while the dependent variable of financial performance was measured using the rate of return on equity, the rate of return on assets and the percentage of financial leverage. For the purpose of analyzing the study data, data panel models were used to test the relationship between independent and dependent variables, and a statistical program (Eviews 10) was used in the data analysis process. The results of the study showed a negative effect for both the ratio of stable deposits to total deposits and the ratio of net loans to total deposits in the rate of return on equity, while it showed a positive effect for both the ratio of stable deposits to total deposits and the ratio of net loans to total deposits in the rate of return on assets, on the other hand, the results of the study found that there is no effect of liquidity risk in the percentage of financial leverage, which indicates that liquidity risk has an impact in the financial performance of private commercial banks in Syria.